Novel chlorine doped graphene electrodes for positive electrodes of a vanadium redox flow battery - Gursu, Hurmus; Gencten, Metin; Sahin, Yucel (WILEY, 2018)
One-step electrochemical preparation of chlorine doped graphene coated electrodes was succeed by cyclic voltammetric method for the first time in the literature in this work. Because hetero atom and oxygen functional groups doped graphene-based electrodes can improve the electrochemical performance of the battery with formed defects sides on the main structure of the electrodes, the modification of graphene-based electrodes by chlorine and oxygen including functional groups such as ?Cl, ?ClO4, ?ClO3, ?OH, and ?CO have been done by arranging of scanned potential in cyclic voltammetric treatment. The structural features of chlorine doped graphene electrodes were analyzed by scanning electron microscopic analysis. Chemical structures of the surface of the electrodes were elucidated by X-ray photoelectron spectroscopy. Raman analyses were carried out to determine the optical properties of the electrodes. Chlorine doped graphene-based electrodes were also used as positive electrode component of a vanadium redox battery for the first time in the literature. The electrodes showed great electrochemical performance as positive electrode materials of the battery.
Keywords: chlorine doped graphene; cyclic voltammetry; graphene electrode; perchloric acid; vanadium redox battery; PENCIL GRAPHITE ELECTRODE; RENEWABLE ENERGY; ELECTROCHEMICAL PREPARATION; IONIC LIQUIDS; OXIDE-FILMS; STORAGE; CARBON; ACID; SUPERCAPACITORS; PRECIPITATION; Energy & Fuels; Nuclear Science & Technology